A Novel Approach to Serial Amnioinfusion in a Case of Premature Rupture of Membranes Near the Limit of Viability - Kohari, Katherine; Mehlhaff, Krista; Merriam, Audrey; Abdel-Razeq, Sonya; Grechukhina, Olga; Leon-Martinez, Daisy; Bahtiyar, Mert Ozan (American Journal of Perinatology Reports, 2018)
Prelabor rupture of the membranes (PROM) near the limit of viability is associated with significant risks for both mother and fetus. Preterm labor, intra-amniotic infection, and placental abruption are the immediate risks to the pregnancy; however, the fetus incurs additional risks related to the sequela of persistent oligohydramnios. Transabdominal intra-amniotic infusions have been studied. Results, suggesting that this intervention may prolong the latency period, and potentially, decrease pulmonary hypoplasia in surviving neonates without evidence of increasing risk of intra-amniotic infection. To our knowledge, the use of antibiotic-infused fluid has not been reported in this clinical scenario. Therefore, we present a case of a patient with PROM before the limit of viability who underwent serial transabdominal amnioinfusions with oxacillin-containing normal saline, which resulted in membrane resealing and neonatal survival with no additional maternal morbidity.
Keywords: periviable PROM; serial amnioinfusion; pulmonary hypoplasia